2007
DOI: 10.1080/10611860601141606
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein mediates brain-to-blood efflux transport of buprenorphine across the blood–brain barrier

Abstract: The involvement of P-glycoprotein (P-gp) in buprenorphine (BNP) transport at the blood-brain barrier (BBB) in rats was investigated in vivo by means of both the brain uptake index technique and the brain efflux index technique. P-gp inhibitors, such as cyclosporin A, quinidine and verapamil, enhanced the apparent brain uptake of [3H]BNP by 1.5-fold. The increment of the BNP uptake by the brain suggests the involvement of a P-gp efflux mechanism of BNP transport at the BBB. [3H]BNP was eliminated with an appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…In vivo and in vitro studies have demonstrated that various opioids, including morphine, fentanyl and methadone, interact with P-glycoprotein (P-gp), ATP-dependent efflux pump, which is highly expressed on the brain capillaries and play a role to decrease the xenobiotic permeation into the brain (58)(59)(60). Recently, it has shown that P-gp-mediated efflux transport system is involved in buprenorphine transport at the BBB in rats (61), which may contribute to non-linear pharmacokinetics in brain to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro studies have demonstrated that various opioids, including morphine, fentanyl and methadone, interact with P-glycoprotein (P-gp), ATP-dependent efflux pump, which is highly expressed on the brain capillaries and play a role to decrease the xenobiotic permeation into the brain (58)(59)(60). Recently, it has shown that P-gp-mediated efflux transport system is involved in buprenorphine transport at the BBB in rats (61), which may contribute to non-linear pharmacokinetics in brain to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Because it isolates efflux processes directly rather than considering efflux as modulator of brain distribution, BEI is an excellent method for determining efflux clearance and studying the mechanisms behind active transport of compounds from the brain. This in vivo method has been extensively used to study the brain efflux clearance of various compounds, including steroid conjugates, valproic acid, nucleoside analogs, buprenorphine, human amyloid-b peptide, and benzylpenicillin and quinidine (Kusuhara et al, 1997;Takasawa et al, 1997;Sugiyama et al, 2001;Kakee et al, 2002;Ohtsuki et al, 2002;Kikuchi et al, 2003;Ito et al, 2006;Suzuki et al, 2007). In our study, we first validated the technique by studying the brain efflux index of valproic acid.…”
Section: Bei Methodsmentioning
confidence: 99%
“…Verapamil is a known Pgp inhibitor widely used to block Pgp function. It was consequently used in cancer combinational therapy [23][24][25]. As shown in figure 4C, verapamil shifted the vinblastine toxicity curve to the left, reaching a calculated GI 50 of 1µM.…”
Section: Cobalamin Decreases Resistance To Vinblastine In Hepg2 Cellsmentioning
confidence: 99%